Tighter Ligand Binding Can Compensate for Impaired Stability of an RNA-Binding Protein - Wallis, C.P.; Richman, T.R.; Filipovska, A.; Rackham, Oliver (AMER CHEMICAL SOC, 2018)
It has been widely shown that ligand-binding residues, by virtue of their orientation, charge, and solvent exposure, often have a net destabilizing effect on proteins that is offset by stability conferring residues elsewhere in the protein. This structure-function trade-off can constrain possible adaptive evolutionary changes of function and may hamper protein engineering efforts to design proteins with new functions. Here, we present evidence from a large randomized mutant library screen that, in the case of PUF RNA-binding proteins, this structural relationship may be inverted and that active-site mutations that increase protein activity are also able to compensate for impaired stability. We show that certain mutations in RNA-protein binding residues are not necessarily destabilizing and that increased ligand-binding can rescue an insoluble, unstable PUF protein. We hypothesize that these mutations restabilize the protein via thermodynamic coupling of protein folding and RNA binding. ©